"Can you do something about the price?" – Exploring the Indian deal and bargaining-prone customer. Issue 5 (10th August 2015) - Dawra, Jagrook; Katyal, Kanupriya; Gupta, Vipin
Abstract : Purpose: – The paper aims to study how deal- and bargaining-prone customers are different from each other. This paper brings out this difference based on psychographics encompassing values – consciousness, price mavenism and personality orientations – needed for special treatment (distinctiveness and play). Design/methodology/approach: – The measurement model was assessed using both exploratory factor analysis and confirmatory factor analysis. The structural model was tested using structural equation modeling. Findings: – This paper finds that value consciousness is a two-dimensional construct in the Indian context. This construct comprises two dimensions of value consciousness, including concern for price and concern for quality. The authors find that deal-prone customers are value conscious and price mavens. Bargaining-prone customers are value-conscious price mavens and have a high need for special treatment (play). Play orientation distinguishes between a deal-prone and a bargaining-prone customer. Research limitations/implications: – The study was limited to grocery products. The consumers surveyed were urban and educated Indians. Practical implications: – With the Indian markets being opened for Western retailers, it is imperative to study the Indian consumers. It is important to understand why the local neighborhood store is able to retain its customer base even when the organized fixed-price formats have been around for approximately 20 years. Originality/value: – This is one of the few papers that tries to understand the Indian consumer's buying behavior, especially with respect to their haggling nature. This paper further develops our understanding of the "deal proneness" and "bargaining proneness" constructs. The authors also study their differences based on psychographics.